2015
DOI: 10.3390/met5010172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strain Localization on Pitting Corrosion of an AlMgSi0.5 Alloy

Abstract: Abstract:The corrosion susceptibility of an age-hardened aluminum alloy in different processing conditions, especially after a single pass of equal-channel angular pressing (ECAP), is examined. The main question addressed is how corrosive attack is changed by strain localization. For that purpose, an AlMgSi0.5 alloy with a strain localized microstructure containing alternating shear bands was subjected to potentiodynamic polarization on a macro-scale and micro-scale using the micro-capillary technique. Pitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Therefore, those microstructural components that changed during the SPD processing caused an enhanced resistance to the dissolution of the material. A similar observation for this alloy was also reported in Nickel et al [ 40 ] It was shown that after ECAP processing, this phenomenon is enhanced due to local microstrains, although the resulting pits are shallower and more homogenous. The reduced size of the pits in the material after ECAP was attributed to cell size.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, those microstructural components that changed during the SPD processing caused an enhanced resistance to the dissolution of the material. A similar observation for this alloy was also reported in Nickel et al [ 40 ] It was shown that after ECAP processing, this phenomenon is enhanced due to local microstrains, although the resulting pits are shallower and more homogenous. The reduced size of the pits in the material after ECAP was attributed to cell size.…”
Section: Discussionsupporting
confidence: 89%
“…With increasing of holding time, the depth of corrosion pits becomes bigger and bigger so that the fatigue crack initiation life of aluminum alloy becomes shorter [9]. Most researchers have previously reported fatigue data of aluminum alloys under pre-corrosion mode based on the equivalent life concept according to airplane structure subjected to two main factors of environment corrosion and fatigue loading [9,[23][24][25]. These results indicated that the differences between the cyclic stress corrosion and prior-corrosion HCF damage behaviors of aluminum alloys are always existent.…”
Section: Fatigue Life Characteristicsmentioning
confidence: 99%
“…Grains smaller than 40 nm have been obtained. o Nickel et al [14] studied the effect of strain localization on pitting corrosion of an AlMgSi0.5 alloy.…”
Section: Open Accessmentioning
confidence: 99%